2023
DOI: 10.1088/1361-665x/acee36
|View full text |Cite
|
Sign up to set email alerts
|

A novel negative stiffness metamaterials: discrete assembly and enhanced design capabilities

Abstract: In this study, a new negative stiffness metamaterial (NSM) is designed using laminates with independent negative stiffness (NS) properties as the functional component and a discrete assembly method. In this paper, the metamaterial is designed by mathematical model, which have been verified and analyzed systematically by experiment and finite element (FE) method. The influence of each laminate parameter on the design of metamaterials under uniform distribution and gradient distribution was investigated, and bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The customized block design, tailored to the specific behavior of the SMs, facilitated better contact between blocks and enhanced the overall stability of the assembly. Future work will explore, test, and improve this approach by considering other SMs and metamaterials [37,38] with greater mechanical properties to fully harness the potential of this approach and achieve optimal deformation in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The customized block design, tailored to the specific behavior of the SMs, facilitated better contact between blocks and enhanced the overall stability of the assembly. Future work will explore, test, and improve this approach by considering other SMs and metamaterials [37,38] with greater mechanical properties to fully harness the potential of this approach and achieve optimal deformation in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of this mechanical metamaterial are beams or shells [52]. The NS behavior is characterized by an increase of compression displacement leading to a load drop, especially usually accompanied by the snap-through behavior caused by the elastic instability [53]. The mechanical metamaterial design of periodic lattices inspired by NS properties achieves desirable dynamic properties [54].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrate novel properties not exhibited by most natural and artificial materials. These properties are usually reversal of common senses, such as negative Poisson's ratio [1,2], negative stiffness [3,4], negative swelling behavior [5], and negative refraction [6,7]. Furthermore, some studies demonstrated how to tune or induce the properties of metamaterials after they are manufactured using temperature [8][9][10], magnetic fields [11], air pressure [12], and other methods, thus achieving more diverse applications.…”
Section: Introductionmentioning
confidence: 99%